EXPLORING ELECTRONIC WASTE RECYCLING INTENTIONS: THE ROLE OF ENVIRONMENTAL CONCERN, PERCEIVED BENEFIT AND ATTITUDE WITHIN THE TPB FRAMEWORK - Promalessy, Rika; Saipul Hadi, T.; Furwanti Alwie, Alvi (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2025)
This study examines the influence of environmental concern (EC) and perceived benefit (PB) on attitude (ATT) and intention to recycle e-waste in Indonesia using the Theory of Planned Behaviour framework. This study also examines the mediating role of attitude in the relationship between EC and PB on intention to recycle e-waste. Data were collected through an online survey of 270 respondents and analysed using the Structural Equation Modeling (SEM) PLS method. The results showed that EC directly and indirectly affects INT through ATT. Meanwhile, PB has no direct effect on intention to recycle e-waste, but significantly shapes ATT, which then acts as a full mediator in increasing recycling intention. These findings suggest that in the context of developing countries such as Indonesia, environmental concern factors are more influential than perceived benefits in encouraging e-waste recycling behaviour. Penelitian ini mengkaji pengaruh environmental concern (EC) dan perceived benefit PB) terhadap attitude (ATT) dan niat dalam mendaur ulang e-waste di Indonesia dengan menggunakan kerangka Theory of Planned Behavior. Studi ini juga menguji peran mediasi attitude dalam hubungan antara EC dan PB terhadap intention to recycle e-waste. Data dikumpulkan melalui survei online terhadap 270 responden dan dianalisis menggunakan metode Structural Equation Modeling (SEM). Hasil penelitian menunjukkan bahwa EC secara langsung dan tidak langsung memengaruhi INT melalui ATT. Sementara itu, PB tidak berpengaruh langsung terhadap intention to recycle e-waste, tetapi secara signifikan membentuk ATT, yang kemudian berperan sebagai mediator penuh dalam meningkatkan niat mendaur ulang. Temuan ini menunjukkan bahwa dalam konteks negara berkembang seperti Indonesia, faktor kepedulian lingkungan lebih berpengaruh dibanding manfaat yang dirasakan dalam mendorong perilaku daur ulang e-waste.